Cardioprotective Effects of Sphingosine-1-Phosphate Receptor Immunomodulator FTY720 in a Clinically Relevant Model of Cardioplegic Arrest and Cardiopulmonary Bypass - Ahmed, Naseer; Mehmood, Adeela; Linardi, Daniele; Sadiq, Soban; Tessari, Maddalena; Meo, Sultan Ayoub; Rehman, Rehana; Hajjar, Waseem M.; Muhammad, Nazeer; Iqbal, Muhammad Perwaiz; Gilani, Anwar-ul-Hassan; Faggian, Giuseppe; et al. (Frontiers in Pharmacology, 2019)
Objective: FTY720, immunomodulator derived from Sphingosine 1 Phosphate has been recently demonstrated immunomodulation, anti-inflammatory and anti-oxidant properties. Furthermore FTY720 might be a key pharmacological target for pre-conditioning. In this pre-clinical model, we investigated the effects of FTY720 on myocardium during reperfusion in an experimental model of cardioplegic arrest and cardiopulmonary bypass. Methods: 30 Sprague-Dawley rats (300-350 grams) were randomized into two groups; Group-A treated with FTY720, 1 mg/kg through I/V cannulation and Group-B, used as control. After 15 mins of treatment(FTY720 and normal saline), rats underwent cardioplegic arrest for 30 mins and followed by initiation of extra corporeal life support for 2 hour, after which support weaning was done and blood & myocardial tissue were collected for analysis. Hemodynamics parameters, inflammatory mediators, nitro-oxidative stress, neutrophil infiltration, Immuno-blotting analysis, Immunohistochemical staining were analyzed and compared between both groups. Results: FTY720 treatment activated the reperfusion injury salvage kinase signaling and survivor activating factor enhancement pathways, leading into decreased cardiomyocyte apoptosis and reduced myocardial oxidative stress. This resulted in improved recovery of left ventricle systolic and diastolic functions. Conclusion: The cardioprotective mechanism in cardioplegic arrest is associated with activation of pro-survival cell signaling pathways that prevents myocardial damage. FTY720 preserves high energy phosphates and improves cardiac function and causes attenuation of myocardial inflammation, and oxidative stress.